Literature in Language Education - Hall, Geoff. author. aut Link
XI, 340 p.
Keywords: A state of the art critical review of research into literature in language education, of interest to teachers of English and modern foreign languages. Includes prompts and principles for those who wish to improve their own practice or to engage in projects or research in this area.